Tuberculosis of breast: scrofulous swelling in the bosom of young women - Patil, Linganagouda S.; N., Hanumanthappa B.; P., Sahana M. (International Surgery Journal, 2021)
Background: Tuberculous breast is a rare extra pulmonary presentation of tuberculosis with nonspecific clinical, radiological and histological findings. The significance of breast tuberculosis lies in its rare occurrence and mistaken identity with breast carcinoma and pyogenic abscess. Methods: A prospective observational study was done to know the incidence, presentation and management modality of tuberculosis of breast. Results: 8 female patients, ranging between 21- 50 years were included, painless lump in breast in 4 patients (50%) was the most common presentation followed by 2 (25%) multiple discharging sinus,1 (12.5%) patient presented as abscess and one had painful lump. Axillary lymphadenopathy seen in 3 (37.5%) patients. All patients had an FNAC but Core needle biopsy or excisional biopsy was definitive for diagnosis. Anti-tubercular chemotherapy was the mainstay of treatment. Conclusions: Breast tuberculosis is an obscure disease and clinical signs can be insidious and non-specific Diagnostic expertise can identify a potentially curable disease of breast tuberculosis.